Biometrics for Network Security - Reid, Paul (Prentice Hall PTR, 2011)
Network security has become the latter-day equivalent of oxymoronic terms like "jumbo shrimp" and "exact estimate." Newspaper headlines are routinely peppered with incidents of hackers thwarting the security put forth by the government and the private sector. As with any new technology, the next evolution of network security has long languished in the realm of science fiction and spy novels. It is now ready to step into the reality of practical application.